2013
DOI: 10.1097/inf.0b013e3182a09b6a
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses in Infants Whose Mothers Received Tdap Vaccine During Pregnancy

Abstract: Maternal Tdap immunization resulted in higher pertussis antibody concentrations during the period between birth and the first vaccine dose. Although slightly decreased immune responses following the primary series were seen compared with controls, differences did not persist following the booster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 18 publications
6
125
1
6
Order By: Relevance
“…1 Given that the UK schedule does not include any further pertussis immunization until children are 3 years old, it is reassuring that the observed differences between the groups had resolved by 12 months of age, a finding also previously reported in term infants. 10 Although post hoc analysis of clinical trial data should be interpreted with caution, these results are biologically plausible and the observed trends are consistent with the recent studies in term infants. 1,3,5,10,11 Our findings, therefore, suggest that maternal vaccination early in the third trimester (ie, closer to 28 weeks' gestation, or even earlier, as administered in some settings 12 ) may 3 Due to the design of the vaccination study, fewer infants were sampled at 5 months of age.…”
Section: Discussionsupporting
confidence: 76%
“…1 Given that the UK schedule does not include any further pertussis immunization until children are 3 years old, it is reassuring that the observed differences between the groups had resolved by 12 months of age, a finding also previously reported in term infants. 10 Although post hoc analysis of clinical trial data should be interpreted with caution, these results are biologically plausible and the observed trends are consistent with the recent studies in term infants. 1,3,5,10,11 Our findings, therefore, suggest that maternal vaccination early in the third trimester (ie, closer to 28 weeks' gestation, or even earlier, as administered in some settings 12 ) may 3 Due to the design of the vaccination study, fewer infants were sampled at 5 months of age.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, in 2012, the ACIP revised the recommendations and advised Tdap vaccine for all pregnant women and for each pregnancy irrespective of the interval between pregnancies (545). Studies have shown that efficient antibody transfer occurred from vaccinated mothers to babies via the placenta, although antibody levels are neither optimum nor long-lasting (545,552,553).…”
Section: Tdap Immunization For Pregnant Womenmentioning
confidence: 99%
“…Nevertheless, it has been observed that immunization with Tdap during pregnancy slightly decreased immune responses after primary doses of DTaP to the infants but the difference did not persist after the following booster doses [17]. The main objective should be to protect infants from severe pertussis, which outweighs the potential risk of suffering the more benign form of pertussis at older ages.…”
mentioning
confidence: 99%